Promotion Architecture: A Deal Fairness Model of Restricted Price Promotions - Yi, Shangwen; Hardisty, David J; Griffin, Dale W; Allard, Thomas (Journal of Consumer Research, 2026)
Abstract This research examines the effectiveness of two common types of restricted price promotions: threshold promotions (conditional on spending more than a threshold amount; e.g., “Get $5 off on orders of $10 or more”) and capped promotions (limited to a maximum dollar value; e.g., “Get 50% off, up to $5 per order”). Results from seven preregistered studies, including one field study, show that threshold promotions lead to higher purchase intentions and conversion rates (but potentially lower purchase amounts) than comparable capped promotions—even though capped promotions are equivalent in maximal economic savings for the consumer—when the trigger value (the spending amount at which the promotion activates or caps) is low. This effect occurs because consumers have higher expected promotion levels for capped promotions and lower expected spending levels for threshold promotions, leading them to perceive the threshold promotion as a fairer deal. However, this effect reverses when the trigger value is high, wherein consumers perceive capped promotions as a fairer deal and prefer them to threshold promotions. The implications of our results for the optimal management of price promotion architectures were discussed.